Peranan Sel Limfosit Dalam Imunulogi: Artikel Review - Flora Ramona Prakoeswa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Lymphocytes are found in blood and lymph. Besides Natural killer (NK) cells, T cells and B cells are the different forms of lymphocytes. Each of these cells plays fundamental role in the body adaptive immune response. B lymphocytes are central players in the immune response; canonically, they have been recognized as precursors of antibody-producing cells: plasma cells. Recent findings have shown that the role of B lymphocytes goes far beyond the production of antibodies. There are different subtypes of B lymphocytes with different participations in innate and adaptive responses that include the recognition of the antigen, its processing, and its presentation to T lymphocytes, as well as the production of cytokines that impact and modulate the response toward the pathogen. Traditionally, it has been considered that B lymphocytes do not have phagocytic abilities that allow them to internalize, to process, or even to be infected by bacterial pathogens. The new information has shown that B lymphocytes can be readily infected by bacterial pathogens and respond to those infections. T lymphocytes play a role in cytotoxic immune responses. They belong to the adaptive immune system and perform a wide array of functions in immune regulation, inflammation and protective immune responses. In recent years, it has been shown that T cells are involved essentially across the entire spectrum of tissue physiology and pathology, not just in reactions or diseases considered to be bonafide immunological, but also, to cite just some examples, in metabolism, in tissue repair, in dysbiosis, and in pregnancy. Basic research on T cells has also sown the seeds that spawned the new era of immunotherapy that is engaging numerous researchers in finding a cure for cancer. The review of this article aims to further understand the latest findings regarding the formation and work mechanism of lymphocytes, especially on adaptive immunity. It summarizes the various forms of lymphocytes and their immunomodulatory roles in health and diseases.